Detection of enoxaparin and argatroban by use of the novel viscoelastic coagulometer ClotPro - Johannes Gratz; Stefan Ulbing; Fabian Schäfer; Stefan Koch; Christoph Dibiasi; Marion Wiegele; Peter Quehenberger; Eva Schaden (Scientific Reports)
Abstract Owing to the simultaneous increase in the risk of thrombosis and bleeding in critically ill patients, point-of-care-available diagnostic tests to guide parenteral anticoagulation are warranted. We evaluated the detection of enoxaparin and argatroban, two commonly used parenteral anticoagulants, using the novel ClotPro viscoelastic coagulometer. For this experimental in vitro study at a tertiary care academic center, blood samples were drawn from twelve (six female, six male) healthy volunteers without intake of antithrombotic medication and no history of hemostatic disorders. Blood samples were spiked with enoxaparin (IU.ml− 1) and argatroban (µg.ml− 1) at increasing concentrations ranging from 0 to 1. The ClotPro Russell’s viper venom (RVV)-test and the ClotPro ecarin (ECA)-test clotting time were performed in parallel with conventional coagulation tests (anti-Xa activity, activated partial thromboplastin time, and diluted thrombin time). We observed a strong correlation between anti-Xa activity and the RVV-test clotting time (r = 0.88 (95% confidence interval (CI) 0.8–0.92; p < 0.001)). Although clotting time cutoff values of 71 and 145 s provided high sensitivity and specificity for detecting anti-Xa activity of ≤ 0.1 and ≥0.6 IU.ml− 1, we found a poor performance at both high and low concentrations. The ECA-test clotting time revealed a very strong correlation with activated partial thromboplastin time (r = 0.96 (95% CI 0.93–0.97; p < 0.001)) and diluted thrombin time (r = 0.97 (95% CI 0.96–0.98; p < 0.001)). The clotting time cutoff values of 86 and 298–431 s provided high sensitivity and specificity for detecting diluted thrombin time values ≤ 0.1 and 0.5-1 µg.ml− 1. Our results suggest that the RVV test is an unreliable method for monitoring enoxaparin treatment, whereas the ECA-test might be an accurate point-of-care alternative for detecting argatroban concentration with potential advantages over standard coagulation tests in terms of point-of-care applicability and turnaround time.